COSTS INCLUDED IN THE PRODUCT PRICE AND THEIR OPTIMIZATION (Marketing Journal, 2025)
The article examines the optimization of costs included in the production cost of goods, as well as the improvement of the cost management system, the selection of priority directions in cost management, and the prevention of cost deviations. In addition, scientific proposals and recommendations have been developed to address existing issues in determining product cost.
Keywords: cost price; production of goods; accounting; management accounting; financial results; expenses; net profit; raw materials